Knee Biomechanics in Individuals With a Recent Concussion During Jump-Landing Tasks. - Chou, Tsung-Yeh; Huang, Yu-Lun; Buckley, Thomas A.; Hafer, Jocelyn F.; Kaminski, Thomas W. (Journal of Athletic Training (KnowledgeWorks Global, Ltd), 2025)
Incomplete neurological recovery following concussion has been linked to increased lower extremity musculoskeletal injury risk. Incorporating cognitive demands into jump-landing tasks may offer better insights into neurological recovery postconcussion and its connection to injury risk. To compare unilateral knee biomechanics during jump-landing tasks across different levels of motor and cognitive demands between individuals with a recent concussion and matched controls. Cross-sectional study. Biomechanics laboratory. We recruited 26 college students with a recent concussion (22 women; age = 19.7 ± 1.2 years; Tegner scale = 7.0 ± 2.2; time since recent concussion = 5.4 ± 3.2 months) and 26 healthy reference participants without a concussion history (22 women; age = 19.9 ± 1.3 years; Tegner scale = 7.0 ± 2.0). Unilateral and limb symmetry of knee biomechanics were assessed during initial ground contact and the landing phase of jump-landing tasks. Limb symmetry was determined by the absolute difference between limbs for knee flexion and abduction angle, internal knee extension and adduction moments, and vertical and posterior ground reaction force. Separate repeated-measure analyses of variance with mixed designs examined group, condition, and group-by-condition interaction, with α =.05. No group differences were observed in most outcome measures for either limb or limb symmetry across all jump-landing tasks except that the concussion history group had lower nondominant peak posterior ground reaction force compared with the healthy reference group (F1,50 = 3.461, P =.016, η2 = 0.111). Both groups demonstrated higher peak knee flexion, abduction angle, and peak knee adduction moments but lower peak knee extension moments and peak vertical ground reaction force on both limbs during double-leg versus single-leg conditions. No other significant findings were observed. The concussion history group demonstrated similar knee biomechanical profiles to the healthy reference group during landing even with added cognitive demands in jump-landing tasks. Elevated lower extremity musculoskeletal injury risk postconcussion may not be detectable through jump-landing biomechanics.